'We Want Light!' Prague Students and the Failing Scientific-Technological Revolution in the Post-Stalinist Era (1956–1968). Issue 1 (February 2022) - Polák, Michael
In the 1960s, the faith in scientific and technological progress pertained to both the Western and the Eastern power bloc. Czechoslovakia was no exception: the scientific-technological revolution was supposed to another step to reaching Communism. The pages of newspapers and magazines were full of articles on the newest scientific and technical discoveries, the automatization and chemization of the industry, and the rationalisation of managing the socialist companies. It was also the faith in expert governance of state and economy that grew in this period: these were supposed to change the position of the scientific specialists and also the students as the future experts. This article follows the way promises connected to the scientific-technological revolution created expectations on the modern student life only to deepen the contrasts between the official declarations and everyday reality. It focuses on several areas of the university environment where the discrepancies were most visible: the lacking equipment of the university building and classrooms, ineffectively managed internships, inflexible placement system, and inadequate material and technical conditions at the university dormitories. These contrasts have also roused the discontent of the students who did not feel recognized. In October 1967, the situation culminated in a demonstration of students from the Strahov dormitory who demanded the repeated blackouts to be solved. The violent suppression of the demonstration resulted in students leaving their patron organization – the Czechoslovak Youth Union – on a large scale and starting autonomous student units independent from both the Union and the Communist Party.